(3GdUMjaI GdSLGOjIs - (3Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH, GdgGTej GdbQTj, CHh GdMSf, GdedbH HRjf GdYGHOjf , (B94 (3g` s
(3ChdgG (B:s
(3MOKfG GdSjO GdBLd fLe GdOjf HgGA GdTQja GdYdhj GdMSfj s
(3BNQgG (B:s
(3CTgO Cfc QH NGdb Gddge CZaQ di hdhGdOj hGQMegG ceG QHjGfi UZjQG hUdi Gddg Ydi eMeO hBd eMeO HQMeJc jG CQMe GdQGMejf s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdchaI (B- (3HZOGO (B(17) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs